ANALISIS KONTRlBUSl RETRlBUSI PENERIMAAN PELAYANAN PASAR TERHADAP RETRlBUSI DAERAH KOTA BANJARMASIN - MAIMUNAH MAIMUNAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This researchwas conducted to determine the contribution, effectiveness, and potential of Market service retribution acceptance on regional retribution in Banjarmasin. The data used in the form of secondary and primary data with research samples selected by purposive random sampling as many as 6 markets from 64 markets in Banjarmasin. This data analysis technique using descriptive analysis with the quantitative method.This result study indicate that the contribution of receipt of market service retribution acceptance on regional retribution in Banjarmasin during the 2011-2017 budget year was still very poor, although the condition of market service retribution in 2016 had a contribution value of 11,510% classified as not good because the percentage value was above 10%. Effectiveness of receiving market service retribution in Banjarmasin tends to fluctuate, it happens in 2011-2017. Potential of receipt of market service retribution on regional retribution in Banjarmasin is 34,82%. The amount of receipt of market service retribution based on regional regulation number 1 in 2016 is 246,89%.Keywords :Market service retribution, contribution, effectiveness, potential, regional retribution.